The Problem of Choice (Change)of the Form of Government in Transition Countries - Kesoyan, H. (Bulletin of Yerevan University C: Jurisprudence, 2020)
The article deals with the problem of the choice (change) of the form of government in transition states. The reasons of changing 61 the form of public government in other countries, as well as theirpolitical and legal backgrounds have been revealed. The study shows that the choice or change in the form of government in transition countries is largely driven by specific circumstances, the need to solve specific problems, which may be based on both objective and subjective motives.
Keywords: Form of government, transitional states, parliamentary governance, constitutional stability, Velvet revolution